Corporate social responsibility initiatives in Nigeria and rural women livestock keepers in oil host communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2018)
Purpose - The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on rural women livestock keepers in the oil producing communities. Design/methodology/approach - This paper employs a quantitative methodology. Data were collected from primary sources using participatory rural appraisal (PRA) technique. The use of participatory research technique in collecting CSR impact data especially as it concerns the small-scale women livestock keeper is based on the fact that it involves the people being studied, and their views on all the issues are paramount. The primary tool used for household survey (collection of the primary data) is a structured questionnaire which is divided into two sections. Section one of the instrument elicited information on the socio-economic characteristics of respondent, while the other section elicited information on the research questions. Both descriptive and inferential statistics were used to analyze the data so as to answer the research questions and test the hypothesis. To answer the research questions, descriptive statistics of measurement of central tendency was used, and the results were presented in tables and charts. While in testing the hypothesis, inferential statistical tool-estimation of logit model (of receipt and non-receipt of MOCs CSR through the GMoU by rural women livestock keepers as function of selected socio-economic and domestic empowerment variables) was used. Findings − The findings shows that GMoU model is gender insensitive as rural women rarely have direct access to livestock interventions except through their husband or adult sons; which is attributed to the cultural and traditional context of the people, anchored in beliefs, norms and practices that breed discrimination and gender gap in the rural societies. Research limitations/implications - The structured questionnaire was directly administered by the researchers with the help of local research assistants. The use of local research assistants was because of the inability of the researchers to speak the different local languages and dialects of the many ethnic groups of Ijaws, Ogonis, Ikweres, Etches, Ekpeyes, Ogbas, Engennes, Obolos, Isokos, Nembes, Okirikas, Kalabaris, Urhobos, Iteskiris, Igbos, Ika-Igbos, Ndonis, Orons, Ibenos, Yorubas, Ibibios, Anangs, Efiks, Bekwarras, Binis, Eshans, Etsakos, Owans, Itigidis, Epies, Akokoedos, Yakkurs, etc, in the sampled rural communities. Practical implication − If the rural women do not feel GMoUs efforts to eliminate discrimination and promote equality in the livestock sector, feminized poverty would create a hostile environment for MOCs in the region. Social implication - The livestock development in Nigeria can only succeed if CSR is able to draw on all the resources and talents, and if rural women are able to participate fully in the GMoUs intervention plans and programmes. Originality/value − This research contributes to gender debate in livestock keeping from CSR perspectives in developing countries and rational for demands for social projects by host communities. It concludes that business has an obligation to help in solving problems of public concern, and that CSR priorities in Africa should be aimed towards addressing the peculiarity of the socio-economic development challenges of the country and be informed by socio-cultural influences.
Keywords: 330; Gender; livestock keepers; corporate social responsibility; multinational oil companies; Nigeria